Integrating the Gap Between Faith Education and Christian Learning in the Indonesian Context with a Christian Worldview - Nelly, Nelly; Siswoko, Edy; Wahyuni, Sara (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
In Indonesia, there is a striking contrast between faith education and Christian learning, which raises major questions regarding integration. Faith education is often associated with worship and character formation in the church, while schools are expected to strengthen Christian values. Understanding Christianity in the concept of worldview is very important, stressing the Christian's responsibility to live in the world, not of the world. This research used qualitative methods, including surveys and thematic analysis, which produced three main findings. First, faith education is usually carried out in religious schools, in line with specific religious doctrines, whereas Christian learning involves systematic exposure to Christian teachings. Second, religious education in Indonesia aims to overcome inter-religious disorders, while Christian education seeks to understand God's will. Research puts forward the concept of a universal worldview as a means of bridging this gap. Three proposed approaches are Teaching for commitment, Teaching for commitment Teaching about commitment, and Teaching from commitment.